PERSEPSI PEDAGANG TERHADAP TATA KELOLA PASAR JALAN H.AGUS SALIM KELURAHAN SUKARAMAI KOTA PEKANBAR - Siti Kurnia Putri; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was carried out on the streets of Agus Salim Pekanbaru. The purpose of this research is to know the management market in Pekanbaru Agus Salim Street in the service of the Market town of Pekanbaru. Topic the focus of this research is to know the perceptions of traders against the activities of trade dibadan way. The sample in this study amounted to 62 people. The author uses quantitative methods and sampling techniques in using Simple Random Sampling. The instrument data is observation and question form. Of research conducted, the authors found that 53.2% of respondents (33orang) who rebuked 1-2 times by related parties.  And the study found that 59.7% of respondents (37 people) who feel insecure when trading. And the researchers found that all respondents (62 people) is obliged to pay retribution. 61.3% of respondents (38 persons) do not know the long trade despite Perda and research also found that 80.6% of respondents (53 people) do not know anyone who manages the party market. 61.3% of respondents (38 persons) said that they never get socialization. The research also found that there are 2 types of poengelolaaan market Market h. Agus Salim managed by the two parties, namely the Government and surrounding communities. The authorities manage requires that money retribution. whereas the community about managing money by asking for security. Keywords: Traders, Market, Social Perception